2022
DOI: 10.1155/2022/5471533
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Yield Components, and Nutritive Value of Perennial Forage Grass Grown under Supplementary Irrigation

Abstract: There is a distinct seasonality in the availability of feeds in the highlands of Ethiopia, reaching a peak and low levels towards the end of the rainy and dry season, respectively. Consequently, this trial was conducted to assess the yield performance and nutritive value of nine perennial grasses accessions from seven grass species under supplementary irrigation to produce feed year-round. The evaluated grasses species were two Urochloa (U. decumbens cv. ILRI-10871 and ILRI-13205), two Setaria (S. sphacelata c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
5
3
5
Order By: Relevance
“…The results were indirectly proportional to the ADF and NDF content ( Figure 6 ). The study was in agreement with the findings of Faji et al [ 26 ],who recorded the RFQ values in the range between 115.07% ( Chloris gyana ) and 122.92% ( Urochloa decumbens ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results were indirectly proportional to the ADF and NDF content ( Figure 6 ). The study was in agreement with the findings of Faji et al [ 26 ],who recorded the RFQ values in the range between 115.07% ( Chloris gyana ) and 122.92% ( Urochloa decumbens ).…”
Section: Discussionsupporting
confidence: 93%
“…According to Singh and Oosting [ 25 ], if the roughage contains above 65% NDF, it is considered as poor quality feed. This supports the findings of Faji et al, Gate et al and Megersa et al [ 20 , 26 , 27 ], who reported that the ADF and NDF contents were in the range of 35.33% ( Panicum aquatica ) to 42.03% ( Panicum coloratum ) and 64.89% ( Panicum aquatica ) to 71.62% ( Chloris gayana ); 29.80% to 52.80% (Bajra x Naiper hybrid) and 61.40% to 77.60% (Bajra x Naiper hybrid); and 42.33% ( Pennisetum unssetm ) to 54.99% ( Pennisetum sp.) and 72.45% ( Eustachys paspaloidsi ), respectively ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 93%
“…Kindu Kosha) varied with location (altitude) from high in Bishoftu to moderately low in Bako, from 12.94 to 9.67 t•ha −1 , respectively. Te current results for the dry matter yield of Desho grass were also lower than those reported in other studies conducted at higher altitudes in Ethiopia [36][37][38]. Tis is in agreement with Mengistu et al (2019), who indicated that highland environments were more ideal for the growth and development of Desho grass species.…”
Section: Discussionsupporting
confidence: 91%
“…Te dry matter yield obtained for Brachiaria decumbens (10.39 t•ha −1 ) in our study was lower than that reported for U. decumbens (11.40 t•ha −1 ) under supplementary irrigation conditions in Holetta, Ethiopia, by Faji et al [36], which might be due to irrigation supplementation. Rhodes grass (Chloris gayana cv.…”
Section: Discussioncontrasting
confidence: 91%
“…Regarding the annual biomass production, the highest dry biomass yield was obtained from highly productive genotypes identified under wet season and drought stress conditions ( Table 5 ). These top biomass-yielding genotypes were tall [ 31 ] with low LSR values, indicating that they had a high stem biomass, although this could, at least in part, be associated with their accelerated development due to their high production. A separate study that agreed with our findings showed that WUE was higher in vigorous genotypes than it was in low-yielding genotypes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%